The Mystery of Yawning in Physiology and Disease - Walusinski, Olivier (Karger, 2010)
Yawning is a stereotyped phylogenetically ancient phenomenon that occurs in almost all vertebrates. As an emotional behavior and an expressive movement, yawning has many consequences; nevertheless, it has so far been poorly addressed in medical research and practice. Bringing together the latest research from many fields, this volume integrates current insights within embryology, ethology, neurophysiology, psychology, fMRI and pathology. The phylogenetic and ontogenetic aspects of yawning offer an interesting perspective on human development, and its occurrence in neurological diseases - an area explored by only a few investigators - may provide useful clinical information. This book will make valuable and fascinating reading to neurologists, sleep specialists, psychologists, ethologists and pharmacologists, as well as to anybody interested in uncovering the mystery of yawning.